Iatrosophist Zeno and Medical Schools of Alexandria in the Fourth Century - Michael Vedeshkin (Hypothekai, 2022)
This article discusses some aspects of the curriculum of medical schools in Late Antiquity, the status of medical schools and the educational space of Late Antique Alexandria in the fourth century AD. The study focusses on the biography of Iatrosophist Zeno of Cyprus, an erudite, rhetor and one of the most famous teachers of medicine in the fourth century, whose biography the sophist Eunapius of Sardis included in his Lives of Philosophers and Sophists. The author opposes the hypothesis established in historiography by W. K. Wright and M. Civiletti, according to which Zeno died before 336, and puts forward new arguments in favor of the fact that he was identical with the archiater Zeno of Alexandria, with whom in 359-361 the rhetor Libanius and the Emperor Flavius Claudius Julian (the Apostate) corresponded. The chronology of the lives of Zeno’s disciples (Oribasius from Pergamum, Ionicus of Sardis, and Magnus of Nisibis) testifies in favor of the fact that the iatrosophist could not have died before 336. In addition, it can be considered proven that Zeno’s of Cyprus school of was based in Alexandria. A successive occupation of the medical chair in the capital of Egypt by two famous iatrosophists named Zeno is not impossible, but highly improbable. Thus, with a high degree of probability, the correspondent of the rhetor Libanius and the Emperor Julian the Apostate was the same Zeno mentioned by Eunapius of Sardis. In other words, Zeno of Cyprus lived at least until the end of 361 AD. In general, the research results allow us to correct the generally accepted dates of the iatrosophist’s life and provide new arguments in favor of R. Penella and J. Giangrande’s assumption that Zeno of Cyprus and Zeno of Alexandria was one and the same person. In addition, the article provides the author's translation of a letter from Libanius to Zeno that has not been published in Russian yet.